Diagnosing Autism Spectrum Disorder: who will get a DSM-5 diagnosis? - G. Kent, Rachel; J. Carrington, Sarah; Le Couteur, Ann; Gould, Judith; Wing, Lorna; Maljaars, Jarymke; Noens, Ilse; van Berckelaer-Onnes, Ina; R. Leekam, Susan (Journal of child psychology and psychiatry, 2013)
Background Introduction of proposed criteria for DSM‐5 Autism Spectrum Disorder (ASD) has raised concerns that some individuals currently meeting diagnostic criteria for Pervasive Developmental Disorder (PDD; DSM‐IV‐TR/ICD‐10) will not qualify for a diagnosis under the proposed changes. To date, reports of sensitivity and specificity of the new criteria have been inconsistent across studies. No study has yet considered how changes at the ‘sub domain’ level might affect overall sensitivity and specificity, and few have included individuals of different ages and ability levels. Methods A set of DSM‐5 ASD algorithms were developed using items from the Diagnostic Interview for Social and Communication Disorders (DISCO). The number of items required for each DSM‐5 subdomain was defined either according to criteria specified by DSM‐5 (Initial Algorithm), a statistical approach (Youden J Algorithm), or to minimise the number of false positives while maximising sensitivity (Modified Algorithm). The algorithms were designed, tested and compared in two independent samples (Sample 1, N = 82; Sample 2, N = 115), while sensitivity was assessed across age and ability levels in an additional dataset of individuals with an ICD‐10 PDD diagnosis (Sample 3, N = 190). Results Sensitivity was highest in the Initial Algorithm, which had the poorest specificity. Although Youden J had excellent specificity, sensitivity was significantly lower than in the Modified Algorithm, which had both good sensitivity and specificity. Relaxing the domain A rules improved sensitivity of the Youden J Algorithm, but it remained less sensitive than the Modified Algorithm. Moreover, this was the only algorithm with variable sensitivity across age. All versions of the algorithm performed well across ability level. Conclusions This study demonstrates that good levels of both sensitivity and specificity can be achieved for a diagnostic algorithm adhering to the DSM‐5 criteria that is suitable across age and ability level.